PENGARUH SUPLAI ARUS LISTRIK DAN JUMLAH SEL ELEKTRODA TERHADAP PRODUKSI GAS HIDROGEN DENGAN ELEKTROLIT ASAM SULFAT - ., Erlinawati; Zikri, Ahmad (KINETIKA, 2014)
Utilization of water as an alternative energy one is to turn it into a gaseous form through the process of electrolysis. To change the water into the gas flow of electrical current needed and plate electrodes to decompose water into hydrogen and oxygen gas. Variations of current are 5, 10 and 15 amperes, while for plate electrodes made with dimensions of 96 cm2. From that problem, the prototype of Hydrogen Fuel Reactor is designed. The purpose of this tool is used to generate hydrogen gas. Flow variations and number plate electrode was used as a fixed variable to calculate how the efficiency of the electricity used, Specific Fuel Consume and percent of energy loss. From the calculation, the hydrogen gas produced increases with the amount of electric current is used, the highest hydrogen gas obtained at 15 ampere current and electrode plate 8 which is 0.2324 moles then the lowest 0.1373 mol at 5 ampere current and electrode 4 plates. From electrical efficiency, increasing according to the number plate electrodes is used. The highest efficiency obtained at 5 ampere current and electrode plate 8 which is 41.2020% and 20.5811% the lowest in 15 ampere current and electrode plate 8. As for the percent of heat loss is inversely proportional to the efficiency, the lower the efficiency of the percent of heat loss is greater, and vice versa. While the value of specific fuel consumption (SFC) increased as the amount of electric current that is used.